2021
DOI: 10.1101/2021.02.14.21251693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The efficacy and safety of Favipiravir in treatment of COVID-19: A systematic review and meta-analysis of clinical trials

Abstract: The novel coronavirus outbreak began in late December 2019 and rapidly spread worldwide, critically impacting public health systems. Several already approved and marketed drugs are being tested for repurposing, including Favipiravir. We aim to investigate the efficacy and safety of Favipiravir in the treatment of COVID-19 patients through a systematic review and meta-analysis. This systematic review and meta-analysis were reported following the PRISMA statement. We registered the protocol in the PROSPERO (CRD4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Our search identified two systematic reviews and meta-analyses that summarized the results of RCTs on favipiravir in hospitalized COVID-19 patients [ 56 , 57 ]. The most recent preprint systematic review and meta-analysis included 9 RCTs (n = 827) comparing favipiravir to any other intervention; out of those, only 3 studies compared favipiravir to usual care or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified two systematic reviews and meta-analyses that summarized the results of RCTs on favipiravir in hospitalized COVID-19 patients [ 56 , 57 ]. The most recent preprint systematic review and meta-analysis included 9 RCTs (n = 827) comparing favipiravir to any other intervention; out of those, only 3 studies compared favipiravir to usual care or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…A review on the safety and efficacy of FRP in COVID-19 patients revealed that there is not a significant difference in LFT changes in the FRP group compared to the comparison group (56). Consistently, a recent meta-analysis study reported FRP leads to non-significantly lower odds for adverse effects compared to placebo (57).…”
Section: Drug-induced Liver Injurymentioning
confidence: 93%
“…In addition, a recent clinical study (N=80) with mild to moderate COVID-19 patients revealed that treatment with Favipiravir led to shorter viral clearance time (4 vs 11 days) and a significant improvement rate in chest imaging (CT) (91.43% vs. 62.22%), were observed [133]. Furthermore, a meta-analysis of nine clinical studies showed significant clinical improvement in the Favipiravir group versus the control group as reflected by viral clearance rate, requirement for oxygen therapy, ICU transfer, and reduced mortality [134]. Favipiravir is approved for COVID-19 in China, India, Japan, and Russia (Table 5)…”
Section: Favipiravirmentioning
confidence: 99%